Reflections on the Discursive Construction of the Identity of the Language Teacher - Sánchez Hernández, Diana Iveth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper presents some insights on the construction of the identity of the university language teacher and their speech. The interest on the topic arises as a reflection on the development of my own identity as a professor as it is framed as part of a larger research project developed within the context of a PhD program whose objective is to find out how, through our discourse, we can not only reflect who we are (or at least who we think we are), the way we see ourselves, and how we would like to be perceived by others, but also how our discourse is the building material of the very thing we want to reflect. This paper discusses briefly some theoretical bases and the historical background of language teaching in Mexico, specifically in two universities: the Universidad Nacional Autónoma de and the Universidad Veracruzana.